PID Controller with an Override Mode for a Wall-Following Robot with a Rotating Sensor Compartment - Sitompul, Erwin; Rohmawan, Elan; Silitonga, Arthur; Bukhori, Iksan (Faculty of Engineering, Universitas Tanjungpura, 2024)
This paper presents the design of a wall-following robot (WFR) with a rotating sensor compartment to reduce the number of distance sensors used. Two infrared (IR) sensors were fitted in the compartment that rotates back and forth at 45 °, producing four measurement values at each rotation cycle. The WFR was regulated using a novel control scheme of PID controller with an override mode. A discrete PID controller in position form was used to run the WFR to follow straight wall segments or walls turning left, while an override mode governed the WFR to follow walls turning right. The sampling time was set to 300 ms. The parameters of the PID controller were tuned using a trial-and-error method. The Mean Absolute Errors (MAE) was selected as the cost function. The WFR conducted twelve trial runs along a trial track with a length of 200 cm, consisting of one right turn and one left turn. The parameters that yielded the lowest MAE of 0.90 cm were used for further tests. Subsequently, a closed track for testing was constructed with a length of 845 cm, consisting of 7 right turns and 2 left turns. The WFR completed five test runs successfully, each elapsing the test track twice. The lowest MAE during the tests was 1.06 cm. The favorable performance of the proposed WFR strengthens future development efforts to equip the robot with more hardware to fulfill specific tasks and to put the completion time into optimization consideration.